2006
DOI: 10.1029/2005gl025366
|View full text |Cite
|
Sign up to set email alerts
|

Role of heterotrophic dinoflagellate Gyrodinium sp. in the fate of an iron induced diatom bloom

Abstract: Iron enrichment to high‐nutrient low‐chlorophyll (HNLC) regions is being considered as a possible way of atmospheric CO2 sequestration to the deep sea. Mesoscale iron‐enrichment to the HNLC subarctic Pacific induced a massive diatom bloom and led to a large decrease in pCO2. In response to the diatom bloom, the heterotrophic dinoflagellate Gyrodinium sp. increased and phagotrophically fed on the diatoms up to 12 times their length. Mathematical simulations show the carbon fixed by diatoms is mostly respired by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 24 publications
(28 reference statements)
1
46
1
Order By: Relevance
“…This observation is consistent with certain feeding strategies being more favorable than others at different times of the year, but more extensive observations are needed to determine if recurrent patterns occur seasonally. Heterotrophic dinoflagellates, such as Gyrodinium spp., have been observed to feed on a wide range of prey types, from pure autotrophs to other heterotrophic organisms such as bacteria and small flagellates (Gaines & Elbrachter 1987, Jacobson 1987, Hansen 1992, Saito et al 2006, Jeong et al 2008. Though dinoflagellates have been observed to be dominant grazers on diatoms (Sherr & Sherr 2007), this may not always be the case in waters near Woods Hole.…”
Section: Discussionmentioning
confidence: 96%
“…This observation is consistent with certain feeding strategies being more favorable than others at different times of the year, but more extensive observations are needed to determine if recurrent patterns occur seasonally. Heterotrophic dinoflagellates, such as Gyrodinium spp., have been observed to feed on a wide range of prey types, from pure autotrophs to other heterotrophic organisms such as bacteria and small flagellates (Gaines & Elbrachter 1987, Jacobson 1987, Hansen 1992, Saito et al 2006, Jeong et al 2008. Though dinoflagellates have been observed to be dominant grazers on diatoms (Sherr & Sherr 2007), this may not always be the case in waters near Woods Hole.…”
Section: Discussionmentioning
confidence: 96%
“…However, an important part of total marine primary production is due to mass phytoplankton blooms dominated by the large-sized and chain-forming species of diatoms which characterize spring and upwelling blooms (Sarthou et al 2005, Barber & Hiscock 2006. Large-sized diatoms also dominate blooms induced by experimental addition of iron in HNLC regions of the sea (Saito et al 2006, Barber & Hiscock 2006 and those episodically observed as a consequence of eddy-driven upwelling (Falkowski et al 1991, McGillicuddy et al 2007. Marine diatom blooms are responsible for most export production, which is significant in terms of both organic sinking flux and food webs supporting marine fisheries (Iverson 1990, Barber & Hiscock 2006.…”
Section: Phytoplankton Blooms In Ocean Ecosystemsmentioning
confidence: 99%
“…Such increasing ratios suggest limitation of microzooplankton biomass during and after bloom peaks. Phytoplankton blooms may be grazed down to some extent by microzooplankton, as described by Tillmann (2004) for coastal blooms of single-cell Phaeocystis sp., and by Saito et al (2006) and Suffrian et al (2008) for a nutrient-stimulated diatom blooms, if protist biomass is not strongly topdown controlled.…”
Section: Top-down Control Of Microzooplankton Biomassmentioning
confidence: 99%
“…They also produce detrital bSiO 2 , which promotes the recycling of Si(OH) 4 in the microbial loop (Schultes et al, 2010). For example, when pallium-feeding thecate dinoflagellates feed on diatoms, they discard the empty silica frustules (Jacobson and Anderson, 1986), whereas athecate dinoflagellates, which directly ingest diatoms, produce mini-fecal pellets composed of the frustules with little associated carbon (Buck and Newton, 1995;Strom and Strom, 1996;Saito et al, 2006).…”
Section: Introductionmentioning
confidence: 99%